Production of Butane from Methyl Ethyl Ketone over Pt/Al2O3 - Zahraa Al-Auda; Keith L. Hohn (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
Methyl ethyl ketone (MEK) was catalytically converted to butane directly in one step over platinum (Pt) supported on alumina (Al2O3). The reaction was performed in the gas phase in a fixed bed reactor. Conversion of MEK to butane was achieved by hydrogenation of MEK to 2-butanol, dehydration of 2-butanol to butene, and further hydrogenation of butene to butane. The results showed that butane can be produced with selectivity reaching 95% depending on the operating conditions. The highest selectivity for butane was obtained at 220 °C and a H2/MEK molar ratio of 15. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).